ANALISIS TREN PRODUKSI DAN KONSUMSI CABAI DI INDONESIA PERIODE 2013–2023 - Muhamad Solekan; M. Aris Pujiyanto; Dwi Putriana Nuramanah Kinding; Faishal Permana; Anggi Fitria Cahyaningsih; Ernes Septina Azizi (Institute of Computer Science (IOCS), 2026)
Chili is a strategic horticultural commodity in Indonesia that contributes significantly to the national economy and inflation formation. The volatile nature of its production often creates an imbalance with stable public consumption patterns. This study aims to analyze the trends and growth rates of chili production and consumption in Indonesia over the 2013–2023 period. A descriptive quantitative approach was applied using secondary time-series data obtained from the Indonesian Central Bureau of Statistics (BPS) and the Ministry of Agriculture. Data were analyzed using the ordinary least-squares linear trend model and annual growth rate calculations. The results indicate that the long-term trend of chili production is positively upward, expressed by the equation Y = 1,564,402 + 141,837X, with actual production shifting from 1,726,382 tons in 2013 to 3,061,260 tons in 2023, yielding an average annual growth rate of 6.05%. On the downstream side, per capita consumption trends also expanded according to the linear equation Y = 3.69 + 0.07X, reaching 4.614 kg/capita/year in 2023 with an average annual growth of 8.63%. However, the consumption data experienced anomalous extreme fluctuations during the 2015–2017 sub-period, indicating methodological recording bias , whereas annual production remained volatile due to climate disruptions (La Nina). The differing growth characteristics between weather-dependent production and population-driven consumption produce daily supply mismatches that trigger seasonal price volatility. Consequently, national chili commodity policy must pivot toward supply management through climate-adaptive agricultural tech, regional cropping pattern calibrations, cold chain system investments, and sector-wide data synchronization.